All Days 2011
DOI: 10.4043/21249-ms
|View full text |Cite
|
Sign up to set email alerts
|

SAFEBUCK JIP - Observations of Axial Pipe-soil Interaction from Testing on Soft Natural Clays

Abstract: This paper outlines recent research into axial pipe-soil interaction from the geotechnical elements of the SAFEBUCK Joint Industry Project. The operational axial pipe-soil friction strongly influences the initiation and cyclic development of lateral buckles, and also controls the magnitude of pipeline end expansions as well as rates of axial walking. Results from model tests performed at the University of Cambridge are presented in this paper, and provide new insights into the axial pipe-soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…The paper by White et al (2011) sets out the work by the SAFEBUCK JIP on the mechanics, behavior and performance of pipelines undergoing axial displacement. Such pipe displacement occurs over time and involves a range of velocity, repeated loading, reversals in direction of movement and variations in vertical pipe load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by White et al (2011) sets out the work by the SAFEBUCK JIP on the mechanics, behavior and performance of pipelines undergoing axial displacement. Such pipe displacement occurs over time and involves a range of velocity, repeated loading, reversals in direction of movement and variations in vertical pipe load.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, in a manner similar to White et al (2011), the findings from this future work will be published with sufficient data to provide more specific guidance for design involving axial pipe-soil interaction. The aim of presenting the framework now is to permit further development within SAFEBUCK based on the data available within the JIP.…”
Section: Introductionmentioning
confidence: 99%
“…Since subsea pipelines generally expand and contract at different velocity under different combination of temperatures and ity [18]. Model tests with three movement velocities are arranged to study the effect, which are 5 mm/hr, 10 mm/hr and 30 mm/hr, respectively, as shown in Table 5.…”
Section: Model Test Programsmentioning
confidence: 99%
“…The coefficients of two parts were recommended as constants without considering the effect of loading rate, the properties of soil and pipe. Model tests were performed to study the axial resistance response of the partially embedded pipe using the polyethylene (PE) pipe with 9 cm diameter and the marine soft clay taken from offshore of West Africa in the SAFEBUCK Joint Industry Project [17,18]. Results showed that equivalent friction factor which is the ratio of friction resistance to submerged weight of pipe varied from 0.1 to 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…White et al 2011) has supported a program of research for tackling the uncertainties associated with the design of pipelines against lateral buckling and axial walking. SAFEBUCK JIP).…”
Section: Introductionmentioning
confidence: 99%